Regulation of the Immune Response by Natural IgM: Lessons from Warm Autoimmune Hemolytic Anemia - Stahl, Dorothea; Sibrowski, Walter (Current Pharmaceutical Design, 2003)
Natural autoantibodies are immunoglobulins of isotypes IgM, IgG and IgA that are present under physiological conditions and that are directed toward self-antigens. Repertoires of self-reactive antibodies have been analysed intensively during the last decade and have been shown to be altered in a variety of autoimmune disorders, immunodeficiency syndromes and lymphoproliferative diseases. Immunoglobulin interactions via variable regions of antibody molecules account significantly for the functional integrity of natural self-reactive antibody repertoires. Recent data indicate that natural immunoglobulins of the isotype IgM might prove particularly useful for the control of antibodymediated autoimmune diseases under certain conditions. Warm autoimmune hemolytic anemia (WAIHA), an IgGmediated autoimmune disorder, turns out to be a clinically relevant in vivo model to analyse the impact of autologous IgM on the development of IgG-mediated autoimmunity in humans. We here summarize current knowledge on the role of autologous IgM for regulating self-reactivity. Since natural self-reactive antibodies are critical for the regulation not only of auto- but also of alloimmune responses, as they occur for example in the setting of organ transplantation, regulation of immune homeostasis by pools of human normal IgM might be an interesting therapeutic target of broad interest for clinical medicine.
Keywords: warm autoimmune hemolytic anemia